Inadekuasi Asumsi Race To The Bottom Pada Kasus Penanaman Modal Asing Di Negara China - Ragil, Hotija Binti (Global and Policy Journal of International Relations, 2014)
ABSTRACTWithin Developing Countries’s scope, China is the first rank of the largest foreign investmentflows (FDI) recipient. Some studies suggest that factor of cheap labour is the pull factor of FDItowards the country. Wage conditions as determinants of the high acceptance of the FDI isalso often called race to the bottom. However, the data in the case of China shows inadequatein these assumptions. The rising cost of China labor in conjuction with rising of FDI. Result ofthe study showed that wage conditions is not the main factor of to gain foreign investmentmarket, but it is competitive advantage factor such labor productivity, the demand for theChinese domestic market that continues to grow and large, and procurement policies oftechnological innovation has became a decisive factor of FDI.Keywords: Foreign investment, productivity, market demand, innovation policyDOI:https://doi.org/10.33005/jgp.v2i02.2071